Harmonising training and development across an industry: the case of Australian rail. Issue 4 (2nd May 2017) - Short, Tom; Harris, Roger McL.
Abstract : Purpose: This paper aims to explore why harmonisation, given its potential, is so difficult to achieve. It analyses the issues and challenges in achieving harmonisation of training and development across an industry. Design/methodology/approach: The approach was a meta-analysis of six research projects undertaken in the Australian rail industry. These projects varied in duration from 12-24 months. Between 2009 and 2013, rail employees in varying roles and levels of seniority, including middle managers, front-line supervisors, rail incident investigators, track workers and drivers, were interviewed ( n = 176) and surveyed ( n = 341). Findings: The meta-analysis identified a range of characteristics associated with harmonisation. It uncovered three categories of harmonisation, seven types of risk modelled in a layered risk pyramid and analysed key structural, environmental and organisational barriers to harmonisation. The paper concludes that harmonisation struggles to gain strategic significance and is hampered by operational pragmatism. Research limitations/implications: There are few published papers examining harmonisation across companies or based on meta-analyses, especially qualitatively. Despite limitations of insufficient detail to allow close analysis, potentially variable quality data across projects from which to develop a meta-analysis and the danger of comparing apples with oranges, more attempts using this approach would be helpful in gaining nuanced insights into an industry. Practical implications: Achieving industry harmonisation requires significant change in the mindset of executives. To enhance the chances of harmonisation, there is need for a strong national entity with overview of the entire industry, high-quality training and development resources and activities and cost-benefit analyses and active campaigns. A major outcome of this research is the risk pyramid, which can be used by managers as a strategic evaluation tool. By using such tools based on sound research, leaders can be equipped to make informed decisions and reduce downstream risks. Originality/value: This research has value in extending the literature in two main ways: through examining the notion of harmonisation across an industry as distinct from within organisations that has been the focus of most studies and through using qualitative meta-analysis in a field dominated by quantitative approaches. It analyses the grey areas between rhetoric about its potential and difficulties in its achievement.